Prosthetic rehabilitation using adhesive bridge and fixed-fixed bridge on the maxilla and telescopic crown overdenture on mandible - Indah Sulistiawaty; Mohammad Dharmautama; Edy Machmud; Jevin S. Cialy; Elvi Elvi (Journal of Dentomaxillofacial Science, 2016)
Prosthetic rehabilitation is the rehabilitation process of masticatory and esthetics function for patients missing teeth and alveolar bone by means of manufacture and installation of dentures. The prosthetic rehabilitation commonly used include denture adhesive bridge, fixed-fixed bridge, as well as telescopic overdenture. Adhesive bridge is bridge denture consisting of single pontic and two retainer wings attached to the abutment using cement or resin. Fixed-fixed bridge is a bridge denture with rigid connectors on both ends of the pontics, whereas the telescopic crown Overdenture is a removable denture that uses linked precision on the original tooth in the form of primary coping on abutment and secondary coping on the denture. To expose the procedures of prosthetic rehabilitation using adhesive bridge and fixed-fixed bridge on the maxilla and telescopic crown Overdenture on mandible. Male patients aged 32 years came with complaints of difficulty to chew food because he had lost some teeth behind. In the maxilla, teeth are lost in the region of 15 and 16 performed by making the fixed-fixed bridge with abutment teeth 14 and 17. Loss of teeth in the region of 26, performed the manufacture of adhesive bridge with a box preparation on the occlusal 25 and 27. In the mandible, tooth loss in the region of 36,37,46, and 47 performed manufacture of telescopic crown Overdenture with primer coping on the teeth 35.38, 45, and 48 and the secondary coping on a metal frame. Prosthetic rehabilitation especially in the case of loss of back teeth is very important because with the denture patients can chew properly and maintain the stomatognathic system.